The sabotaging role of myeloid cells in anti-angiogenic therapy: coordination of angiogenesis and Immune suppression by hypoxia - Li, Chunyan; Bazhin, Alexandr V. (Journal of cellular physiology, 2017)
Tumor angiogenesis has become a promising target for anti-tumor therapy. Unfortunately, the somewhat inevitable occurrence of resistance has limited the efficacy of anti-angiogenic therapy. In addition to their well-established role in immune suppression, bone marrow-derived myeloid cells actively contribute to tumor angiogenesis. More importantly, myeloid cells constitute one of the major mechanisms of resistance to angiogenesis inhibition. As the most pervasive feature in tumor microenvironment, hypoxia is able to initiate both pro-angiogenic and immunosuppressive capacities of myeloid cells. Tumor adapts to hypoxic stress primarily through signaling mediated by hypoxic inducible factors (HIFs) and consequently utilizes hypoxia to its own advantage. In this regard, hypoxia orchestrates both angiogenesis and immune evasion to support tumor growth. In this article, we will review available information on the sabotaging role of myeloid cells in anti-angiogenic therapy. We will also discuss how hypoxia coordinates the dual-role cellular and molecular participants in microenvironment to maximize the efficiency of angiogenesis and immunosuppression to promote tumor progression. J. Cell. Physiol. 232: 2312-2322, 2017. © 2016 Wiley Periodicals, Inc.
Gesehen am 12.11.2018
First published: 09 December 2016